Internationalization of LIS program through strategic partnership - Mansor, Yushiana; Ismail, Nooraini (2009)
The demand of the global market has resulted into the development of many internationalization initiatives in the educational sector, including the library and information science field (LIS). The Department of Library and Information Science (DLIS), International Islamic University Malaysia (IIUM) is committed towards achieving the mission of the university, i.e. Integration, Islamization, Internationalization, and Comprehensive Excellence. The paper reports on the recent development at the DLIS in the effort to enhance the marketability of its graduates.